(untitled) (diségno, 2021)
This work aims to investigate the essential principles and generative systems of imaginary drawing with particular reference to the production created between 1960 and 1990 and depicting flying, dynamic, suspended, floating architectures, free from any law of physics.The hand and the drawing can see things that the eye has not yet seen, materialize the impossible, conceive something that, perhaps, could exist only in the distant future and on distant mental planes: these creation depict spaces that can exist only on paper (hence "paper architecture"). These architectural ‘evocation’ drawings, however, also have a real design value and, although far-fetched, represent the object of a profound research carried out by several visionary authors-artists-architects such as Ron Herron, Peter Cook, Constant Nieuwenhuys or Yona Friedman and later Raimund Abraham, Lebbeus Woods and, in some proposals, Aldo Rossi. All these authors mentioned above investigate the marginal design but with different purposes, values and models therefore the graphic results vary a lot. In the space of the sheet of paper where everything is possible, the compositional and aggregation principles of architecture become a virtuosity free from the physical limitations of the reality in which we live, a space in which the authors, fascinated by the sky, even come to make buildings and cities hover in the air.